2007
DOI: 10.1093/jmedent/44.6.1086
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles kleini,Anopheles pullus, andAnopheles sinensis: Potential Vectors ofPlasmodium vivaxin the Republic of Korea

Abstract: Anopheles sinensis Wiedemann (63.3%) was the most abundant Anopheles mosquito captured at cowshed resting collections in malaria high-risk areas (northern Gyeonggi Province) near the demilitarized zone (DMZ) in Korea during 2005, followed by Anopheles kleini Rueda (24.7%) and Anopheles pullus M. Yamada (8.7%). At cowshed resting collections in malaria low-risk areas (Jeonnam and Gyeongnam provinces), An. sinensis accounted for 96.8% of all Anopheles spp. collected, followed by An. kleini Rueda (2.7%), whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
51
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 18 publications
0
51
2
Order By: Relevance
“…lesteri, and An. yatsushiroensis are vector mosquitoes in Korea (Ree et al 1967;Shin et al 2002;Lee et al 2007). However, the susceptibility of different mosquitoes to the subtypes of P. vivax is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…lesteri, and An. yatsushiroensis are vector mosquitoes in Korea (Ree et al 1967;Shin et al 2002;Lee et al 2007). However, the susceptibility of different mosquitoes to the subtypes of P. vivax is not well known.…”
Section: Introductionmentioning
confidence: 99%
“…However, a malaria vaccine is not yet available (PATH 2009). Of the eight anopheline mosquito species in South Korea (Joshi et al 2009), Anopheles kleini Rueda, Anopheles pullus M. Yamada, and Anopheles sinensis Wiedemann are considered as the primary vectors of P. vivax malaria near the Korean Demilitarized Zone (Lee et al 2007). In particular, An.…”
mentioning
confidence: 99%
“…5 Plasmodium vivax malaria rapidly increased to a high of 4,142 cases by 2000, before declining to 864 cases by 2004. 2,[6][7][8][9][10][11] Malaria steadily increased to 2,227 cases by 2007, but decreased to 811 by 2011. 11 Although Anopheles spp.…”
mentioning
confidence: 99%
“…Preliminary data also suggests that An. kleini may be a principal vector of P. vivax malaria near the DMZ, 10 as laboratory studies found that An. kleini produced many sporozoites.…”
mentioning
confidence: 99%